Assessment of consumer perspectives on the use of paper packaging in Trinidad. - Farrah Mathura; Rohanie Maharaj (PLoS ONE)
Background Paper packaging is increasingly being used to replace single use plastics to mitigate the negative effects of plastic pollution on the environment. While many developed countries have made considerable strides in this transition, developing countries, like Trinidad, have lagged behind, partly, due to no stringent legislation for types of packaging at commercial outlets. Objectives The objectives of this study were to investigate the demand for and assess public perceptions of sustainable paper packaging in Trinidad. Methodology Data were collected using a Knowledge, Attitudes, Practices (KAP) survey supplemented by interviews, packaging stress testing, and analysis via SPSS. Results A majority of participants demonstrated awareness of recycling knowledge (79%) and deforestation awareness (84%); which aligns with the 71% of participants who considered themselves environmentally conscious. The attitudes and practices of participants did not correlate directly with their environmentally conscious behaviour such as willingness to purchase paper-based food containers (67%), finding paper packaging more aesthetically pleasing than plastic (73%) and willingness to pay more for paper packaging (53%). The interviews highlighted a demand for sustainable paper packaging while also identifying challenges such as waterlogging of packaging, sustainable raw materials sourcing, packaging strength, and the need for customer testing and feedback. The stress test showed good appearance and durability. Conclusions Overall, the sustainable paper packaging stress test received favourable feedback and there were varying levels of knowledge, attitudes and practices related to sustainable packaging. Future research can build on the current findings and the questionnaire can be replicated after the introduction of replacement of single use plastics with non-wood paper packaging.